2000
DOI: 10.1039/b001153n
|View full text |Cite
|
Sign up to set email alerts
|

Fast urinary screening for paracetamol using on-line microwave assisted hydrolysis and spectrophotometric detection

Abstract: A fully automated urinary screening system for paracetamol and its metabolites is proposed. The method comprises on-line acid microwave assisted hydrolysis of the drug to p-aminophenol followed by reaction with o-cresol in alkaline medium. The indophenol blue dye formed can be continuously monitored at 620 nm. The detection limit achieved, 0.1 microgram ml-1, allows a high dilution of the samples, thus reducing potential interferences from the sample matrix (mainly protein degradation during urine hydrolysis).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…Recently, automated methods were used for such reagent based colorimetric detections. Criado et al, 28) Chen et al, 34) Bocxlaer et al 31) and Morris et al 35) developed a fully automated urinary screening system for the quantitative determination of paracetamol. Although it was reported in Bocxlaer's paper 31) that p-aminophenol is easily oxidized to p-iminoquinone forming the basis of such assays, coupling with resorcinol in alkaline medium to convert into an indophenol dye would naturally yield higher absorptivity and lower detection limits.…”
Section: Spectrophotometric Determination Of Paracetamol In Urine Witmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, automated methods were used for such reagent based colorimetric detections. Criado et al, 28) Chen et al, 34) Bocxlaer et al 31) and Morris et al 35) developed a fully automated urinary screening system for the quantitative determination of paracetamol. Although it was reported in Bocxlaer's paper 31) that p-aminophenol is easily oxidized to p-iminoquinone forming the basis of such assays, coupling with resorcinol in alkaline medium to convert into an indophenol dye would naturally yield higher absorptivity and lower detection limits.…”
Section: Spectrophotometric Determination Of Paracetamol In Urine Witmentioning
confidence: 99%
“…Urinary screening of PCT is mostly based on acidic [25][26][27][28][29][30] or enzymatic [31][32][33] hydrolysis of PCT to PAP, the latter requiring 17-20 h. In most of the conventional spectrophotometric procedures, the hydrolysis product (PAP) reacts with a special chromogenic reagent in basic medium to form an indophenol blue dye. A number of chromogenic reagents including phenol, 30) o-cresol, 25,26,28) Heirwegh and Fevery,29) in strongly acidic medium, PAP resulting from differential extraction and acid hydrolysis of total PCT in urine is diazotized and the diazonium salt cou- In the present paper, conventional spectrophotometry in conjunction with cloud point extraction-preconcentration were investigated as alternative methods for paracetamol (PCT) assay in urine samples. Cloud point extraction (CPE) was employed for the preconcentration of p-aminophenol (PAP) prior to spectrophotometric determination using the non-ionic surfactant Triton X-114 (TX-114) as an extractant.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement of the pharmacokinetic data of paracetamol formulations using urinary excretion data has been well documented [3,7,8,[11][12][13][14] and could be achieved without the discomfort, possible hazard and necessary attendance of medical staff required for repeated venipunctures. Recently, Criado et al [15] reported a fully automated urinary screening system for paracetamol and its metabolites which comprises on-line acid microwave assisted hydrolysis of the drug to p-aminophenol followed by reaction with o-cresol in alkaline solution; the indophenol blue dye formed was monitored at 620 nm. Another optical technique, such as spectrofluorimetry, although more sensitive, also requires the use of derivative reactions [16] because paracetamol is not an intrinsic fluorophor.…”
Section: Introductionmentioning
confidence: 99%